Produktivitas Pemboran Inpit pada Bukit Everest 9N2/TB.19005, 9N2/TB.19001, 9N2/TB.19002 dan 9N2/TB.19004 di PT. ANTAM Tbk. UBPN SULTRA - Muhammad Dian; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. Drilling is an important activity in the mining industry where by making a hole perpendicular or tilted from the ground to a predetermined depth. Drilling carried out by PT. ANTAM Tbk. UBPN SULTRA is a production drilling carried out to obtain ore samples or samples that are available to determine the amount of ore content and thickness at that location, this drilling is known as inpit drilling. Inpit drilling is carried out in areas that have been developed. Effectiveness and efficiency of inpit drilling activities during operations are needed to obtain optimal results in drilling activities. The condition of the equipment as well as the working time needed for the drilling activity flow is a very big influence on the productivity of inpit drilling. From processing data in drill holes 9N2/TB.19005, 9N2/TB.19001, 9N2/ TB.19002 and 9N2/TB.19004 the drilling effectiveness was 98.31%, 96.76, 97.66% and 98.44%. Drilling productivity was 8.93 m/hr, 7.06 m / hr, 6.01 m / hr and 5.76 m / hr, respectively. As well as core recovery inpit drilling for each drill hole is 96.92%, 93.08%, 100% and 88.46%.Keywords: Drilling Productivity, Geomin drilling, Inpit Drilling, Ore, Revenue Reserved